Application of Remote Sensing in Geographical Research - yosufi, Mohammadkazem (Journal of Natural Sciences – Kabul University, 2020)
Remote sensing techniques have emerged as effective tools for the systematic survey, analysis, and better management of natural resources, along with monitoring desertification, floods, droughts, and landform changes. This technology documents dynamic changes in physical processes and the resulting landforms, typically using satellite imagery. This paper provides a general overview of remote sensing. While this technique has been applied to beaches, valleys, and other landforms, a historical examination of human social life shows that humanity has advanced through activities such as agriculture and animal husbandry. As a result, new technologies shorten the distance between humans and nature, making human activity more active. The use of remote sensing in different geographical locations accelerates human activities and, in some areas, regulates this expansion and restriction. New technology has improved the field of remote sensing in these applications.